1994
DOI: 10.1590/s0103-90161994000300019
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de métodos de colheita e da localização dos frutos na planta sobre a ocorrência de sementes duras em quiabeiro (Abelmoschus esculentus (L.) Moench)

Abstract: RESUMO:A ocorrência de sementes duras em quiabeiro (Abelmoschus esculentus (L.) Moench) foi estudada em função da colheita única dos frutos na senescência das plantas ou da colheita periódica dos frutos no estádio de maturação morfológica. As cultivares utilizadas foram "Amarelinho", "Santa Cruz-47" e "Campinas-2 IAC 4076" e os frutos foram separados em aqueles provenientes da haste principal e os oriundos dos ramos laterais. A porcentagem de sementes duras foi avaliada por meio do teste padrão de germinação e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
5
0
3
Order By: Relevance
“…Line, 20.1.2, also with angular pods, although presenting decrease in germination and increase in hardseedness, expressed them in a much lesser degree than the other lines with angular pods. No hardseedness was observed among lines with round pods in any stage of development, in agreement with Setubal et al (1994), who did not find hardseedness in cultivar Santa Cruz 47 55 DAA.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Line, 20.1.2, also with angular pods, although presenting decrease in germination and increase in hardseedness, expressed them in a much lesser degree than the other lines with angular pods. No hardseedness was observed among lines with round pods in any stage of development, in agreement with Setubal et al (1994), who did not find hardseedness in cultivar Santa Cruz 47 55 DAA.…”
Section: Resultssupporting
confidence: 88%
“…Pereira (1975) verified that seeds from pods located in the middle of the plant presented higher germination capacity than those extracted from pods located in plant ends and ramifications. Looking for information about pod maturation, Setubal et al (1994) concluded that, regarding seed production, the most adequate stage for pod harvesting is between 45 and 55 days after anthesis (DAA) for cultivars Campinas-2, Santa Cruz 47 and Amarelinho. In the case of cultivar Santa Cruz 47, Castro (2005) observed that seed quality decreased in pods harvested between 34 and 41 DAA without a post harvest resting period.…”
Section: Germination and Hardseedness Of Seeds In Okra Elite Linesmentioning
confidence: 99%
“…In contrast, Demir (1997) reported that okra seeds failed to germinate until 32 DAA, and the highest germination percentage was observed when seeds were harvested at 39 and 43 days after anthesis. Setubal et al (1994) observed that the proportion of hard seeds increased significantly when the harvesting was delayed until the senescence of the plant. Passam et al (1998) reported that premature or late harvesting of pods results in reduced seed germination.…”
Section: Introductionmentioning
confidence: 99%
“…As altas taxas de germinação em menor tempo para a cv. Amarelinho pode ser explicada pela menor incidência de sementes duras, face a maior permeabilidade do tegumento, que segundo Setubal et al, (1994), é nula nessa cultivar. A cv.…”
Section: Resultsunclassified